PENGARUH PENDEKATAN HUMANISTIK TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Karwadi, Karwadi; Indrawan, Deni (STIT AL MULTAZAM, 2023)
Motivation in the learning process is needed so that students can be enthusiastic in learning. This research uses ex-post-fact quantitative method. The population in this study were fourth-grade students at MI Matlaul Atfal with a total of 23 students. The use of the sample itself with the total sampling technique where all the population is taken. Collecting data in this study used a questionnaire with a Likert scale. The data analysis technique used is an inferential statistical analysis which includes prerequisite testing and hypothesis testing. The results showed that 58.7% of student activity in PAI learning was influenced by the humanistic approach with a correlation value of 0.761 in the strong category. Even though the correlation value of student activity is in a strong category, it must always be increased not only in PAI learning but in other learning.